Effect of mechanical ventilation on central venous pressure measurement among adult post-open heart patients - Montemayor, Maria Giselle S.
Objectives. The usual practice in CVP measurement of mechanically ventilated patients is to remove the ventilator to measure the CVP during exhalation phase. The main purpose of this study was to find an alternative but acceptable method to measure the CVP when a patient is hooked to a mechanical ventilator. The specific research objectives are as follows: (1) To determine the effect of mechanical ventilation on CVP values among adult post-open heart patients; (2) Find out if there were variations in the CVP value when taken at different phases of the respiratory cycle; and (3) To identify a certain phase in the respiratory cycle during mechanical ventilation which coincides with the end-exhalation CVP measured during spontaneous breathing.Design. This study utilized a quasi-experimental design. This design was utilized because the independent variable was manipulated in terms of the setting of mechanical ventilator and measured at the inspiratory and expiratory phases of respiration.Sampling. Subjects of this study included adult post-open heart patients in a tertiary hospital. These patients were selected because these patients were routinely hooked to a mechanical ventilator with a hemodynamic monitoring line post-operatively. Also, these patients follow the same course of treatment and recovery. All patients aged 18 and above, and scheduled for open-heart surgery were included in the study. Patients were excluded if the CVP line was malfunctioning (determined by the right atrial waveform display via a hemodynamic monitor and catheter tip placement confirmed by x-ray); and if the participant was hemodynamically unstable (BP 90 mm Hg and 150 mm Hg and CR 60/min or 120/min). Of the twenty-five (25) post-open heart patients, only thirteen (13) patients qualified and finished the data gathering procedure.All CVP values were measured manually via a print out of the CVP waveform using a strip chart recorder located at the nurses' station. All hemodynamic pressures utilized the transducer system of monitoring connected to a flushing device and a hemodynamic monitor.Data gathering. Data gathering began once the patient exhibited eye opening and/or movement of extremity. A 10-minute stabilization period followed thereafter before measurements were started. For each patient, data were collected in two (2) phases. The first phase sought to determine if there were fluctuations in CVP during undisturbed conditions. CPV was measured every 5-minutes over a 25-minute period. The second phase sought to compare CVP on ventilator and CVP with spontaneous breathing (off ventilator). In this phase, CPV was measured sequentially on-ventilator, off-ventilator, post-off ventilator, 1-minute after, 5-munites after and 10-minutes after. Two values were extracted for each ventilator setting, i.e. inhalation CVP and exhalation CVP (the two phases of the respiratory cycle). Three sets of data were gathered for each participant.To control extraneous factors that may similarly affect CVP values and to ensure patient's safety throughout the data collection procedure, a stabilization period was allowed before the measurement of CVP. Ten minutes were allowed for any change in the patient's position, 2-minutes if the patient coughed within 2-minutes of the next CVP reading, and 5-minutes if endotracheal/nasotracheal occurred within 5-minutes of the next CVP reading. If the patient was on positive expiratory end pressure (PEEP), the level of PEEP was subtracted from the actual value of the on-ventilator CVP during the exhalation phase.Data Analysis. Mean CVPs were computed for each participant and subjected to statistical treatment. In phase I, after subjecting the data to a One-way Repeated Measures ANOVA, no significant differences (a0.05) were observed in the CVP values.